Kajian Teologis Makna Berkat Dalam Ritual Ma’ta’da Dengan Makna Berkat Kekristenan - Grace Barbara Randa Tangyong (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2023)
Culture makes an area unique from other areas. Indonesia is a country that has a lot of diversity, especially in terms of cultural diversity. The Toraja tribe is a tribe that has its own uniqueness, especially in death which is full of rituals. One of the rituals that is still preserved by the Toraja people, especially in Tumbang Datu District, North Sangalla, is Ma'ta'da. The Tumbang Datu community is predominantly Christian, however the Tumbang Datu community still preserves ma'ta'da rituals/customs as an ancestral heritage that must be maintained. Ma'ta'da is a ritual that is carried out once a year as a means of worshiping ancestors, paying vows, and asking for blessings from ancestors so that they will be blessed in their lives. People's belief in ancestors who are a source of help and blessings for them, is contrary to Christian teachings which state that Jesus Christ is the source of salvation and blessings for believers. The aim of this research is to reveal the meaning of ma'ta'da and its relationship with theological meaning in Christianity and to build a theological understanding of the meaning of the ma'ta'da ritual. This research uses a qualitative research method using an interview approach with local traditional leaders. Ma'ta'da is interpreted by the people of Tumbang Datu as a form of gratitude for the blessings given by the Ancestors/To Membali Puang to their family. In Christianity, blessings only come from God.